2000
DOI: 10.1590/s0034-71082000000400005
|View full text |Cite
|
Sign up to set email alerts
|

Mercury content in shark species from the South-Eastern Brazilian coast

Abstract: We present here the first results of Hg concentrations in three small shark species (Rhizoprionodon lalandei, R. porosus and Mustelus higmani) from the SE Brazilian coast. Mercury concentrations in R. lalandei ranged from 21.5 to 280.0 ng.g -1 dry weight (d.w.) (average 74.6 ng.g -1 d.w.; 17.9 ng.g -1 wet weight). In R. porosus, concentrations ranged from 7.6 to 90.5 ng.g -1 d.w. (average 42.2 ng.g -1 d.w., 9.4 ng.g -1 wet weight), whereas in M. higmani, concentrations ranged from 13.0 to 162.8 ng.g -1 d.w. (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 16 publications
4
20
1
6
Order By: Relevance
“…The Hg concentrations observed in Australian shark species and Atlantic C. signatus corroborated the hypothesis that Hg concentrations could be related to diet and depth because C. signatus was a semi-pelagic species that inhabits environments deeper than 100 m and feeds mainly on demersal teleost fish. Lacerda et al (2000) found lower Hg concentration values for the coastal shark species Rhizoprionodon lalandei, R. porosus and Mustelus higmani from the north coast of Rio de Janeiro State, Brazil (Table 1). The lower Hg concentrations could be due to aspects of the three species' life-histories, including living at shallower depths on coastal environments, smaller body size (23-100 cm), and different feeding habits compared to C. signatus.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The Hg concentrations observed in Australian shark species and Atlantic C. signatus corroborated the hypothesis that Hg concentrations could be related to diet and depth because C. signatus was a semi-pelagic species that inhabits environments deeper than 100 m and feeds mainly on demersal teleost fish. Lacerda et al (2000) found lower Hg concentration values for the coastal shark species Rhizoprionodon lalandei, R. porosus and Mustelus higmani from the north coast of Rio de Janeiro State, Brazil (Table 1). The lower Hg concentrations could be due to aspects of the three species' life-histories, including living at shallower depths on coastal environments, smaller body size (23-100 cm), and different feeding habits compared to C. signatus.…”
Section: Resultsmentioning
confidence: 95%
“…Several studies have already shown that mercury can bioaccumulate in muscle tissues of fish, mainly in the methylated form. Mercury concentrations in fish generally present a positive correlation with size and age Ward and Neumann, 1999;Lacerda et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Resultados similares foram reportados para o manguezal do estuário do Rio Mucuri, Bahia, onde as espécies apresentaram fatores de concentração variando entre 2,2 e 2,6 para Zn e entre 1,7 e 3,2 para Cu (Cuzzuol & Campos 2001). Lacerda et al (1986) observaram que ao longo da costa sudeste brasileira, os fatores de concentração para metais pesados em espécies de mangue foram inferiores a 1,0, sendo maiores em Avicennia schaueriana do que em Rhizophora mangle, o que foi em parte confirmado no presente estudo. Os autores demonstraram falta de correlação entre as concentrações de metais nas folhas e no sedimento, fato também observado no manguezal do Estuário do Rio São Mateus.…”
Section: Discussionunclassified
“…Por outro lado, observa-se que áreas que servem como criatório de peixes e outros organismos marinhos estão contaminadas de forma significativa por mercúrio, um metal capaz de ser biomagnificado ao longo da cadeia trófica, o que pode explicar estimativas de contaminação do pescado em níveis acima dos recomendados pela OMS [57][58][59] . Além disso, estudos realizados sobre a mobilização do Hg em ambiente costeiro demonstram que esse metal pode ser remobilizado de sedimentos mais profundos 41,60,61 e alcançar a coluna d'água, onde se mantem associado, por exemplo, à matéria orgânica, passível de ser incorporado pela biota 18,19,62,63 .…”
Section: íNdice De Geoacumulação Regional De Hg Na Costa Brasileiraunclassified